Students and workers in May of 68 - Bernardo, João (Pontifícia Universidade Católica de São Paulo, 2008)
May of 68 is generally presented as a student movement, forgetting that at that moment there also occurred the largest general strike in French history. This article attempts to demonstrate that the theme of the working class and capitalist exploitation was decisive even within the student component of the movement.